Dilematis Perencanaan Karir Mahasiswa Akhir Pendidikan Agama Islam - Arfin Fuad Afdhol (Mahesa Research Center, 2021)
The purpose of this research is to deepen in real terms the main factors of the unmatangan of student career planning. So that it can be an evalution for the development of the Education process in islamic religious education courses oriented to career maturity. This research is a research method library (library research) and a method called double movement which according to Sutrisno (2006) the core of the research method using the principles of the Qur'an which is then applied in modern life. The source of this study is divided into two, namely primary and secondary. The primary source is the Text of alqur'an relating to the theme of research, while the source of the secondary is related to books, journals, websites, previous research and literature that has relevance to the theme of this research. The results showed that the need for the application of surah Al-haysr verse 18 which explains the need for man to always intropeksi himself for what has been done today for a better tomorrow.